Meningkatkan Minat Belajar Matematika Melalui Permainan Edukatif pada Siswa SD Kristen Sera - Sigit Sugiarto; Michael Inuhan; Arche F. Bonara; Sisilia M. Taihuttu; Ince Wattimury; Renny Souhoka; Sefanya Sairiltiata (Lembaga Pengembangan Kinerja Dosen, 2025)
The low mathematics learning outcomes of students are caused by many factors, one of which is the low interest in learning mathematics. One way to increase students' interest in learning mathematics is to apply educational games in the mathematics learning process. This description encouraged the PkM team to carry out community service at SD Kristen Sera with the aim of increasing students' interest in learning mathematics through educational games. This community service was carried out on Friday, December 13, 2024, which was attended by 17 grade VI students. The success of this activity was measured using a questionnaire on students' interest in learning mathematics. The results of the analysis of the learning interest questionnaire data showed that there was an increase in students' interest in learning mathematics before and after participating in the learning process using educational games on the material on integer operations. This shows that the application of educational games in the mathematics learning process needs to be done.